COOPERATIVE LEARNING MODEL TAKE AND GIVE TYPE TO IMPROVE LEARNING SCIENCE RESULTS FOR STUDENTS CLASS V UPTD SPF SD N 179 TALUMAE SOPPENG REGENCY - Shasliani, Shasliani; Pasinggi, Yonathan S; Asyla, Putri Nur (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
The problem in this research is how to apply the take and give type cooperative learning model to improve the science and science learning achievement of grade V students of UPTD SPF SD Negeri 179 Talumae, Soppeng Regency. This research is graderoom action research which aims to determine the process and results of implementing the take and give type of cooperative learning model to improve science learning achievement for grade V students and to determine the increase in learning achievement in grade V material by implementing the cooperative learning models. take and give type. The approach used in research is a qualitative approach. The data collection techniques used are observation, tests and documentation. The research subjects were grade teachers and 18 students. The carried out in two cycles. In cycle I, the research results on the learning process were at sufficient qualification (C) and the learning test results were at sufficient qualification (C). Cycle II research results on the learning process were in good qualifications (B) and learning test results were in good qualifications (B). The conclusion of this research is that the application of the take and give type cooperative learning model can improve the science and science learning process and achievement of grade V UPTD SPF students at SD Negeri 179 Talumae, Soppeng Regency